The fishery for Norway lobster off the portuguese coast: a biological and economic assessment - Leocádio, Ana Maria Colaço (2011)
Dissertação de mest., Aquacultura e Pescas, Faculdade de Ciências do Mar e Ambiente, Universidade do Algarve, 2009